2011
DOI: 10.1111/j.1744-6163.2011.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mindfulness Meditation in Promoting a Culture of Safety on an Acute Psychiatric Unit

Abstract: Increases in patient satisfaction and decreases in patient safety events were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 32 publications
2
92
0
5
Order By: Relevance
“…All studies included participants working in a healthcare setting, including nursing (Bazarko et al, ; Horner et al, ), nursing and midwifery (Foureur et al, ) and mental health (Brady et al, ). Several studies used a variety of HCPs, including nurses, doctors and occupational therapists (Fortney et al, ; Manotas et al, ; Martín‐Asuero & García‐Banda, ; Schenstrom et al, ; Shapiro et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies included participants working in a healthcare setting, including nursing (Bazarko et al, ; Horner et al, ), nursing and midwifery (Foureur et al, ) and mental health (Brady et al, ). Several studies used a variety of HCPs, including nurses, doctors and occupational therapists (Fortney et al, ; Manotas et al, ; Martín‐Asuero & García‐Banda, ; Schenstrom et al, ; Shapiro et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the largest study involving 239 employees (Wolever et al 2012), participants receiving mind-body interventions showed greater improvements compared to controls on perceived stress, self-reported sleep quality, and heart rhythm coherence, a measure of autonomic balance. Positive results have also been reported for mindfulness-based interventions for healthcare staff (Cohen-Katz et al 2005; Krasner et al 2009; Pipe et al 2009; Shapiro et al 2005), including decreased job burnout (Cohen-Katz et al 2005) and decreased personal stress levels (Brady et al 2012; Pipe et al 2009). …”
Section: Introductionmentioning
confidence: 91%
“…Workplace studies have also shown that psychological stress contributes to poor morale, absenteeism, and high staff turnover (Limm et al 2011; Michie and Williams 2003; Noblet and Lamontagne 2006). In mental health treatment settings, stress may also negatively impact the staff-patient relationship and the healing environment, interfering with staff’s ability to effectively communicate with and understand the patient and thereby reduce care outcomes (Brady et al 2012; Garman et al 2002). Because of the evidence for the harmful effects of workplace stress, there has been increasing research on stress management interventions for improving physical and mental well-being and morale and reducing burnout and turnover in a variety of settings (Limm et al 2011; Wolever et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…28 41 While one study reported reductions in patient safety events such as aggression, falls, and medication errors, these were not statistically analysed. 21 There were insufficient number of studies to examine the combined effect of meditation on healthcare professional empathy, 33 43 job satisfaction 28 41 or patient safety events. 21 Both studies utilising mental health scales found statistically significant improvements in self-reported mental health after mindfulness training.…”
Section: Interventions Effects By Outcome Measurementsmentioning
confidence: 99%
“…21 There were insufficient number of studies to examine the combined effect of meditation on healthcare professional empathy, 33 43 job satisfaction 28 41 or patient safety events. 21 Both studies utilising mental health scales found statistically significant improvements in self-reported mental health after mindfulness training. 24 41 Heterogeneity Q statistics were statistically significant for controlled trials of self-efficacy (tables 4 and 5).…”
Section: Interventions Effects By Outcome Measurementsmentioning
confidence: 99%